2020
DOI: 10.1016/j.tsf.2019.137751
|View full text |Cite
|
Sign up to set email alerts
|

A practical method to characterize proton exchange membrane fuel cell catalyst layer topography: Application to two coating techniques and two carbon supports

Abstract: The coating technique and the type of carbon support can strongly affect the surface topography, the homogeneity and the thickness of the catalyst layers of Proton Exchange Membrane fuel cells. These features can in turn strongly modify the local diffusion properties of the layer and the final cell performance, but literature about catalytic layers does not often address such issues. This work aims at studying the topography of proton exchange membrane fuel cell catalyst layers by means of 3D characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…8(a) blue line). Additionally, the difference in homogeneity across configurations is consistent with the results obtained by Deschamps et al [42], who compared the topography of sprayed layers obtained with 2 configurations of run paths and with an accumulation of 160 run paths at 33 mm height. It should be noted that the authors needed a large accumulation of layers to reach an average thickness of 6.3 µm with the commercial carbon XC-72R from Cabot ® .…”
Section: Spray Configurationssupporting
confidence: 89%
See 2 more Smart Citations
“…8(a) blue line). Additionally, the difference in homogeneity across configurations is consistent with the results obtained by Deschamps et al [42], who compared the topography of sprayed layers obtained with 2 configurations of run paths and with an accumulation of 160 run paths at 33 mm height. It should be noted that the authors needed a large accumulation of layers to reach an average thickness of 6.3 µm with the commercial carbon XC-72R from Cabot ® .…”
Section: Spray Configurationssupporting
confidence: 89%
“…In addition, the topology of the coatings can change depending on the spray pattern. Deschamps et al [42] tested two spraying configurations with and without spacing at the nozzle return and showed that the topology of the obtained deposited layers varies with the spraying configurations, suggesting a possible variation in PEMFC performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it imposes higher requirements on the manufacturing process. 32,33 Several methods have been proposed for the preparation of MEAs, including scraping, 34 transfer printing 35 and spraying. 36 Park et al 37 demonstrated a scraping method via a pre-expanded PEM, and the results showed that the height and speed of the scraper can be adjusted according to the state of the paste, to realize the reproducibility of the scraping process.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these materials are characterized by having high porosity and surface area, controllable pore size, and also having the possibility of being shaped as desired 22 , 23 . These attributes make CXs attractive materials for several applications, including fuel cells 24 , 25 , catalysis 26 – 28 and adsorption for both water treatment 29 , 30 or analytical chemistry 31 , 32 . Regarding water treatment by adsorption, some authors have been studying CXs for removal of specific PSs and CECs: (i) Moral-Rodriguez et al 33 studied different CXs for the adsorption of diclofenac; (ii) Álvarez et al 34 applied CXs as adsorbents for the removal of caffeine and diclofenac; and (iii) Carabineiro et al 35 studied the adsorption capacity of CXs for the antibiotic ciprofloxacin.…”
Section: Introductionmentioning
confidence: 99%